The Circulation of Ancient Animal Resources Across the Yellow River Basin: A Preliminary Bayesian Re-evaluation of Sr Isotope Data From the Early Neolithic to the Western Zhou Dynasty - Wang, Xueye; Roberts, Patrick; Tang, Zihua; Yang, Shiling; Storozum, Michael; Groß, Marcus; Fernandes, Ricardo (Frontiers in Ecology and Evolution, 2021)
Abstract: Many questions still remain regarding the acquisition and circulation of ancient domesticated animals across the Yellow River Basin, one of the key areas for the development of complex societies in ancient China. Here, we re-evaluate previously published strontium isotope data (87Sr/86Sr, n = 167) from tooth enamel of domesticated animals at 10 archaeological sites in the Yellow River Basin to shed new light on the transition between the Neolithic (7000–5000 BCE) and the Western Zhou Dynasty (1046–771 BCE). The results show that from the Late Neolithic to the Western Zhou Dynasty, some domestic animals, mostly cattle and sheep, were increasingly sourced from non-local areas. We present the bioavailable Sr isoscape for the Yellow River Basin produced using Bayesian modeling methods, and demonstrate the considerable diversity in the origins of these non-local domestic animals, some of which may have come from locations hundreds of kilometers away from the site as early as the Late Neolithic. The increasingly variable 87Sr/86Sr ratios of domestic animals from the Neolithic to the Western Zhou Dynasty are consistent with that of associated human remains, and also match the archaeological and zooarchaeological evidence for increased circulation of animal products in the Yellow River Basin. Therefore, we infer that economies increasingly incorporated non-local animals as part of wider circulation networks that emerged with the development of complex societies since the Late Neolithic.